Hubungan Antara Masa Kerja dengan Carpal Tunnel Syndrome pada Pembatik Tulis di Kampung Batik Giriloyo Bantul - Surya Darma Budiono; Ana Budi Rahayu; Taufiek Hikmawan Yuliarto Benni Sambada (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Batik tulis is one of Indonesia’s cultural heritages with high artistic and philosophical value, whose production process still relies heavily on manual activities using a traditional tool called canting. The batik-making process involves repetitive hand movements and prolonged working duration, which may increase the risk of musculoskeletal disorders, particularly Carpal Tunnel Syndrome (CTS). This study aimed to determine the relationship between working period and the incidence of Carpal Tunnel Syndrome among handwritten batik artisans in Giriloyo Batik Village, Imogiri, Bantul, and to describe the characteristics of working period and CTS incidence among the workers. This study employed a descriptive analytic quantitative method with a cross-sectional design. The research was conducted from July to August 2024 and involved 39 respondents selected based on inclusion and exclusion criteria. Data were collected using respondent identity questionnaires and the Boston Carpal Tunnel Questionnaire (BCTQ) to assess CTS symptoms. Data analysis included univariate and bivariate analyses using the chi-square test. The results showed that most respondents were female (97.3%), aged 40–60 years (64.1%), and worked less than 8 hours per day (66.7%). Most respondents with a working period of ≥4 years experienced CTS complaints (69.2%). Statistical analysis showed a significant relationship between working period and CTS incidence (p=0.028; p<0.05). The intensity of CTS symptoms also tended to increase with longer working periods. These findings highlight the importance of preventive efforts through ergonomic improvements and reducing exposure to repetitive movements among batik artisans.